2017
DOI: 10.1177/1460458217735676
|View full text |Cite
|
Sign up to set email alerts
|

mHealth technologies for osteoarthritis self-management and treatment: A systematic review

Abstract: Osteoarthritis is a common chronic disease that can be better treated with the help of self-management interventions. Mobile health (mHealth) technologies are becoming a popular means to deliver such interventions. We reviewed the current state of research and development of mHealth technologies for osteoarthritis self-management to determine gaps future research could address. We conducted a systematic review of English articles and a survey of apps available in the marketplace as of 2016. Among 117 unique ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 45 publications
1
62
0
Order By: Relevance
“…Importantly, recent osteoarthritis treatment and management guidelines endorse patient self-management as a means to increase self-awareness of symptoms and better prepare patients to assume active roles in shared medical decision making [ 8 ]. mHealth can enable patient self-management through the use of wearable aides for activity monitoring and behavioral change using personalized, real-time feedback [ 9 ], through acquisition of new knowledge, and by enhancing patient-provider communication [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, recent osteoarthritis treatment and management guidelines endorse patient self-management as a means to increase self-awareness of symptoms and better prepare patients to assume active roles in shared medical decision making [ 8 ]. mHealth can enable patient self-management through the use of wearable aides for activity monitoring and behavioral change using personalized, real-time feedback [ 9 ], through acquisition of new knowledge, and by enhancing patient-provider communication [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-management in the form of digitally supported rehabilitation is a striking candidate for digital interventions supporting patients with musculoskeletal pain [ 9 ]. Proof-of-concept studies have consistently shown promising results in terms of clinical endpoints such as pain reduction for patients engaging in the app.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 26 included articles, one reported a priori protocol registration 7 and four stated reporting was based on the PRISMA guideline for systematic reviews. 7,30,37,39 Adam 20 World of Urology Prostate Cancer Athilingam 21 JMIR Cardiology a Heart Failure Bhattarai 22 Pain Medicine Arthritic Pain Garcia-Cruz 23 Actas Urologicas Espanolas Men's sexual disorders Jupp 24 Pediatric Blood and cancer Cancer/Oncology Lee 25 JMIR mHealth and uHealth a Chronic Kidney Disease Luo 26 Journal of Clinical Rheumatology Rheumatoid Arthritis Rey 27 Neurologica Parkinson's Disease Svendsen 28 Journal of Dermatological Treatment Psoriasis Choi 29 Health Informatics Journal a Osteoarthritis Grainger 30 JMIR mHealth and uHealth a Rheumatoid Arthritis Martinez 31 JMIR Diabetes a Diabetes Rossi 32 mHealth a Diabetes Sobnath 33 JMIR mHealth and uHealth a Chronic Obstructive Pulmonary Disease Xie 34 JMIR mHealth and uHealth a Cardiovascular Disease Arnhold 35 JMIR a Diabetes Brouard 36 Annals of Medicine Cancer Brzan 37 Journal of Medical Systems a Diabetes Con 38 JMIR mHealth and uHealth a Inflammatory Bowel Disease Machado 7 Best Practice and Research Clinical Rheumatology Low back pain Fijacko 39 Journal of Medical Systems a Type 2 Diabetes Lee 40 British Journal of Sports Medicine Concussion Wurzer 41 Burns Burns Vega 42 PLOS One Pain Wallace 43 Journal of Opioid Management Chronic Pain El-Gayar 44 Journal of Diabetes Science and Technology Diabetes a Journals listed in field of 'Medical Informatics' in InCites Journal Citation Reports (Clarivate Analytics, 45 or published in subsidiary journal of JMIR.…”
Section: A Priori Review Registration and Registration Guidelinementioning
confidence: 99%